Прогнозирование показателей надежности двухкаскадного термоэлектрического охлаждающего устройства в режиме Q0max - Zaykov, V. P.; Kinshova, L. A.; Kazanji, L. D.; Khramova, L. F. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The parities for an estimation of parameters of reliability two-cascade ТED of a various design depending on their basic parameters in a mode Q0max are received. The results of accounts for differences of temperature ΔТ=60, 70, 80 K in view of thermal loading and temperature dependence of parameters, and also in a mode of the thermal pump (at ΔТ=0) are given. The estimation of maximal cooling capacity two-cascade TED of a various design for various conditions of operation is carried out.